Structural evolution in a pyrolitic magma ocean under mantle conditions - Huang, Dongyang; Murakami, Motohiko; Brodholt, John; McCammon, Catherine; Petitgirard, Sylvain (Earth and Planetary Science Letters, 2022)
Structure and properties of terrestrial magma oceans control the co-evolution of the core, mantle and atmosphere of the early Earth, but are poorly understood because discrepancies remain between experiments and theoretical calculations. Here we combine acoustic velocity measurements and ab initio simulations on pyrolite glass/melt with a silicate Earth-like composition. In the complex system, we find a gradual increase of sound velocity with increasing pressure. Through ab initio simulations, this is explicable by the transition from four- to six-fold coordinated Si occurring over the entire mantle regime. These results are at odds with recent X-ray diffraction measurements, which show an abrupt change in Si-O coordination at 35 GPa. It is however consistent with recent high-pressure data, where Ni partitioning between molten metal and silicate exhibits a similar gradual change with pressure. Unlike amorphous silica, smooth structural evolution in a multicomponent system implies progressive changes in magma ocean properties with depth, such as density, element partitioning and transport properties, which, when incorporated into magma ocean models, may improve our understanding of early history of the Earth and other rocky planets.
Keywords: ab initio; acoustic velocity; diamond anvil cell; early Earth's interior; magma ocean; silicate melt structure